Determination of the optimal distillation sequence of a ternary mixture incorporating heat integration by means of Microsoft Excel Solver. Issue 6 (11th April 2021) - Vázquez, Ana; Briones, Laura; Morales, Victoria; Iglesias, José; Morales, Gabriel; Escola, José M.
Abstract: Nowadays, the computer skills acquisition by Chemical Engineering (ChE) students is based on practical uses of specialized software packages in different applications. Process optimization courses use high‐level algebraic programming languages, such as GAMS (General Algebraic Modeling System) or AMPL (A Mathematical Programming Language), which are usually reserved for advanced programs in ChE degrees or ChE M.Eng. Commercial software for process optimization has several benefits, such as the possibility of facing complex numerical problems in a more efficient and straightforward way. By contrast, they typically present expensive license fees, and students usually require intense training to get the proper user‐level skills. The use of simpler and economic software tools may help overcoming these limitations. In this context, Microsoft (MS) Excel Solver tool is a widespread software with the potential to be used worldwide by any ChE student, and with the power to solve complex optimization problems at the academic level. In this paper, we introduce the application of MS Excel Solver for the optimization of a distillation sequence for the separation of a ternary mixture, including the heat integration in the definition of the problem. This is an MINLP problem, which usually requires specialized software performing stochastic methods, such as Simulated Annealing, to achieve a solution. In this regard, the approach to solve an optimization problem using the MS Excel Solver tool shown in this study was successfully employed by a student of ChE M.Eng. at Rey Juan Carlos University and the Autónoma University of Madrid in the development of her master thesis.